Permeability Properties of Jointed Rock with Periodic Partially Filled Fractures - Fei Ye; Jun-Chao Duan; Wen-Xi Fu; Xing-Yu Yuan (Geofluids)
Rock fractures always influence the hydrological properties of a rock mass. To investigate the seepage characteristics of a rock mass with partly filled fractures, a mathematical model is established. In this model, the clear fluid in fractures is governed by the Navier-Stokes equation, and the fluid both in the porous medium and rock matrix are subjected to the Brinkman-Extended Darcy equation. The analytic solution of an equivalent permeability coefficient for a rock mass with partly filled fractures is solved, and it could be reduced to some special known results. Comparisons with experimental data show good agreement, thus verifying the validity of the present computations.